Estimating the population structure of Javan rhinos (Rhinoceros sondaicus) in Ujung Kulon National Park using the mark- recapture method based on video and camera trap identification - Adhi Hariyadi; Agus Priambudi; Ridwan Setiawan; Daryan Daryan; Asep Yayus; Hendra Purnama (Pachyderm)
The population structure of the Javan rhino (Rhinoceros sondaicus) in Ujung Kulon National Park (NP) in Banten, Indonesia was assessed using visual identification and mark-recapture estimation. The software program CAPTURE was used for selecting the best fit estimator for the mark-recapture calculation and yields M(th) as the best model. The software results delivered a mean estimation of 32 rhinos (a minimum of 29 and maximum of 47 rhinos) with a 95% confidence level based on the dataset obtained from April 2008 to September 2009. The visual identification suggests that the current population in Ujung Kulon NP is male biased by a 3:2 sex ratio of males versus females. The demography shows that the population consists of mainly adult individuals that have a tendency of 1% population growth per year.